Literatur Review: Efektivitas Metode Pijat Oksitosin Dan Power Pumping Terhadap Peningkatan Produksi Asi Sebagai Aktivitas Harian Pada Ibu Bekerja - Juniarti, Elda; Flora, Rostika; Zulkarnain, M. (Syntax Literate, 2025)
Workplace breastfeeding support and breast milk production enhancement methods, such as oxytocin massage and power pumping, play an important role in the success of exclusive breastfeeding. This study aimed to assess the effectiveness of various breast milk production enhancement methods and workplace breastfeeding support for working breastfeeding mothers. This literature review was conducted by identifying, selecting, and analyzing relevant studies related to oxytocin massage, power pumping, and workplace breastfeeding support. Data were collected from various sources of scientific literature, and studies were selected based on predetermined inclusion criteria. The results showed that oxytocin massage and power pumping methods significantly increased milk production and supported the success of exclusive breastfeeding. Workplace breastfeeding support also proved effective in helping working mothers continue breastfeeding. Oxytocin massage and power pumping methods are effective in increasing milk production, while workplace breastfeeding support is important for successful exclusive breastfeeding among working mothers. Implementation of workplace breastfeeding support policies needs to be improved to support maternal and infant health.